The contingent valuation study of Heiðmörk, Iceland – Willingness to pay for its preservation. (1st March 2018) - Cook, David; Eiríksdóttir, Kristín; Davíðsdóttir, Brynhildur; Kristófersson, Daði Már
Abstract: The decision-making and policy formation context in Iceland has been largely devoid of total economic valuations in cost-benefit assessments. Using an internet survey and applying the double bounded dichotomous choice methodology, this contingent valuation study sets out an estimate of the total economic value pertaining to Heiðmörk, a popular recreational area of urban open space located on the fringes of Reykjavík, Garðabær and Kópavogur. In so doing, this case study advances the practice of using non-market valuation techniques in the country. The welfare estimates provide evidence that Icelanders consider Heiðmörk to possess considerable total economic value, with taxpayers willing to pay a mean lump-sum tax in the range 17, 039 to 24, 790 ISK per payment to secure its preservation, equating to an estimated total economic value of between 5.87 and 35.47 billion ISK. In the light of possible competitive land management demands among Heiðmörk's three owners and many recreational users in the future, the establishment of these values and their potential use in cost-benefit assessments informs the debate concerning whether the area should be preserved or further developed to satisfy economic objectives. Additionally, a body of experimental evidence is formed suggesting that the increased duration of a fixed payment vehicle is associated with much higher total economic valuations compared to a one-year payment period. Highlights: The contingent valuation study on Heiðmörk progresses use of the method in Iceland. Willingness to pay to preserve Heiðmörk estimated in range 5.87–35.47 billion ISK. Evidence of limited sensitivity of scope to the duration of a fixed payment vehicle.